2003
DOI: 10.1002/cncr.11737
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis of esophageal carcinoma to the brain

Abstract: BACKGROUND Esophageal carcinoma rarely metastasizes to the brain. The objectives of the current study were to assess the frequency of brain metastasis from an esophageal primary tumor, to determine correlates of survival, and to describe treatment modalities and their outcomes. METHODS Between June, 1993 and July, 2001, 1588 patients with a primary esophageal carcinoma registered at The University of Texas M. D. Anderson Cancer Center; of those, 27 patients (1.7%) had a diagnosis of brain metastasis. The autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
91
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 33 publications
7
91
2
Order By: Relevance
“…1 Fifty percent of newly diagnosed patients have unresectable or metastatic disease at the time of diagnosis, typically to the lungs, liver, and adrenal glands. 8,[10][11][12] Brain metastasis from esophageal cancer remains a rare occurrence with approximately 100 clinical cases reported in the world literature (Table 1). Metastatic spread to the brain likely occurs via Batson's vertebral venous plexus, which provides communication between the esophagus and central nervous system (CNS).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…1 Fifty percent of newly diagnosed patients have unresectable or metastatic disease at the time of diagnosis, typically to the lungs, liver, and adrenal glands. 8,[10][11][12] Brain metastasis from esophageal cancer remains a rare occurrence with approximately 100 clinical cases reported in the world literature (Table 1). Metastatic spread to the brain likely occurs via Batson's vertebral venous plexus, which provides communication between the esophagus and central nervous system (CNS).…”
mentioning
confidence: 99%
“…Metastatic spread to the brain likely occurs via Batson's vertebral venous plexus, which provides communication between the esophagus and central nervous system (CNS). 5,8,10 Clinical cohort studies have identified brain metastases in up to 2.1% of esophageal cancer cases and in 1% to 5% of patients in postmortem studies. [13][14][15][16] Weinberg et al 8 reported on 1588 patients treated at The MD Anderson Cancer Center between 1993 and 2001, and identified only 27 patients (1.7%) with esophageal cancer brain metastases, 19 (70%) of whom had concurrent systemic disease.…”
mentioning
confidence: 99%
See 3 more Smart Citations